2022
DOI: 10.1029/2022jc018972
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Scale Spatial Variations of Air‐Sea Heat, Moisture, and Buoyancy Fluxes in the Tropical Trade Winds

Abstract: Observations from two autonomous Wave Gliders and six Lagrangian Surface Wave Instrument Float with Tracking drifters in the northwestern tropical Atlantic during the January–February 2020 NOAA Atlantic Tradewind Ocean‐atmosphere Mesoscale Interaction Campaign (ATOMIC) are used to evaluate the spatial variability of bulk air‐sea heat, moisture, and buoyancy fluxes. Sea surface temperature (SST) gradients up to 0.7°C across 10–100 km frequently persisted for several days. SST gradients were a leading cause of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 69 publications
3
6
0
Order By: Relevance
“…Section 3.4 shows an impressive oceanic thermal imprint on the near-surface layer in the submesoscale regime, which is consistent with recent case studies in denoting the submesoscale air-sea coupling (Acquistapace et al, 2022;Gaube et al, 2019;Iyer et al, 2022;Shao et al, 2019). Compared to the case studies, the positive relationship observed between filter-derived SST perturbations and other variables such as wind, air temperature, and heat flux provides evidence for the existence of submesoscale air-sea coupling in a general context.…”
Section: The Uncertainties In Submesoscale Air-sea Couplingsupporting
confidence: 85%
See 1 more Smart Citation
“…Section 3.4 shows an impressive oceanic thermal imprint on the near-surface layer in the submesoscale regime, which is consistent with recent case studies in denoting the submesoscale air-sea coupling (Acquistapace et al, 2022;Gaube et al, 2019;Iyer et al, 2022;Shao et al, 2019). Compared to the case studies, the positive relationship observed between filter-derived SST perturbations and other variables such as wind, air temperature, and heat flux provides evidence for the existence of submesoscale air-sea coupling in a general context.…”
Section: The Uncertainties In Submesoscale Air-sea Couplingsupporting
confidence: 85%
“…The mesoscale SST-wind coupling processes have been relatively extensively investigated in previous studies (see reviews by R. D. Small et al (2008); Seo et al (2023)), but the smallscale oceanic forcing (below the deformation radius) on the MABL processes is only beginning to be investigated (Czaja et al, 2019). Recently, both observations (Acquistapace et al, 2022;de Szoeke et al, 2021;Gaube et al, 2019;Iyer et al, 2022;Shao et al, 2019;Yang et al, 2024) and simulations (Conejero et al, 2024;Strobach et al, 2022;Sullivan & McWilliams, 2022;Sullivan et al, 2020;Wenegrat & Arthur, 2018) have shown that submesoscale SST variability can have direct impacts on the MABL, including surface wind speed, air-sea heat flux, and cloud formation (Acquistapace et al, 2022). The energetic submesoscale processes in the Southern Ocean also implied the strong submesoscale air-sea coupling (Siegelman et al, 2020;Su et al, 2018;Swart et al, 2023), but it remains largely unexplored, particularly from the observation perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4a shows a schematic of a SWIFT track drifting through an intermittent field of saturated (with visible optical surface signature) and diffused (without visible optical surface signature) bubble clouds during a 512‐s burst of data along which echogram data are collected in a surface‐following reference frame. The buoy has a “wind slip” velocity relative to the surface water U slip ≈ 0.01 U 10 N that is caused by wind drag on the portion of the buoy above the surface (Iyer et al., 2022). Note that the example SWIFT track shown here is calculated with respect to the earth frame, so the example includes both the true surface current and the wind slip of the buoy (which combine together to make the observed drift velocity of the buoy, typically U drift ≈ 0.04 U 10 N ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, mesoscale to submesoscale SST spatial anomalies still exist ubiquitously in daily satellite SST analysis in the EUREC 4 A/ATOMIC area, albeit with a weak magnitude compared to the coastal North Brazil Current (NBC) rings (Fratantoni and Glickson 2002). In situ SST measurements from wave gliders in this wintertime ATOMIC campaign estimated SST variability up to 0.78C across an order of 10-100 km with a maximum gradient of (0.0478C km 21 ) (Iyer et al 2022a). Similar SST variability was also observed on board NOAA ship Ronald H. Brown in ATOMIC (Fig.…”
Section: Introductionmentioning
confidence: 83%